Comparison Between Food Security in Indonesia and Thailand: Rice Export and Import - Sri Herliana; Sudrajati Ratnaningtyas; Qorri Aina; Umi Zuraida; Acip Sutardi; Syifaya Qorina (Journal of The Community Development in Asia, 2025)
This paper examines the food security of Indonesia and Thailand, focusing on rice production, consumption, population, exports, and imports. Despite rice being a staple food in both countries, Thailand has achieved a surplus in rice production and serves as a major exporter, while Indonesia faces challenges in meeting its rice demand due to high population growth and inefficient production systems. Thailand’s success is attributed to its advanced agricultural infrastructure, strict quality control, and robust government support. Conversely, Indonesia, although having a larger arable land area, struggles with inefficient farming practices and high rice consumption, leading to a reliance on rice imports, primarily from Thailand. This study uses a comparative analytic design, relying on secondary data from government reports, academic journals, and trade databases. The findings suggest that Indonesia can improve its food security and move toward self-sufficiency by adopting Thailand’s practices, including modernization of farming techniques, policy support, and infrastructure development. The paper emphasizes the need for strategic investments in agricultural modernization and policy adaptation to bridge the production-consumption gap in Indonesia